Examining the relationships of destination image, memorable tourism experience and tourists' behavioral intentions in ancient towns - Xue, Zhou; Siew, Imm Ng; Jo, Ann Ho (2023)
The image of a destination plays a significant role in tourists' judgments and selections. The key latent variable must be identified by analyzing the relationships between a destination's image and the decisions made by visitors to optimize destination marketing strategies. Using the ancient towns of Chengdu, Sichuan, China, as the research object, this study establishes the causal relationship between destination image, memorable tourism experience, and visitors' behavioral intentions using the SOR model. The results indicate that destination image influences tourists' behavioral intention via the mediator effect of memorable tourism experience and that tourists' place attachment moderates the relationship between memorable tourism experience and behavioral intention. In addition, because Chengdu's ancient towns are popular destinations for local tourists on short excursions, this study selects local tourists as the sample collection object. It verifies the applicability of the memorable tourism experience scale in the context of ancient towns. In addition, based on the Two-factor theory, this study adopts an alternative classification of destination cognitive image. It verifies the varying degrees of influence of destination motivator and hygiene image factors on memorable tourism experiences and behavioral intention, with implications for future research and destination marketing and management in culturally similar regions.